(untitled) (Fiep Bulletin - online, 2014)
The metabolic syndrome, also known as syndrome X, insulin resistance syndrome, or syndrome plurimetabólica deadly quartet, is characterized by the group of cardiovascular risks, and in accordance with the publication of the World Health Organization (WHO) and the American Association the Diabetes in 1998 apud (BENELLI, Vanessa Raquel et al, 2006), are considered carriers of metabolic syndrome subjects with glucose intolerance, the normal glucose tolerance with diabetes or insulin resistance and two of the following changes: use of anti-hypertensive and / or high blood pressure (> 140/90 mmHg), obesity (body mass index> 30 kg/m2) abdominal (waist-hip ratio> 0.90 in men and> 0.80 in women), high levels of triglycerides (> 150 mg / dl), glucose above 100 mg / dl, low HDL-cholesterol (<35 mg / dl in men and <39 mg / dl in women), total cholesterol> 200mg/dL, and microalbuminuria urinary excretion albumin of> 20 mg / min). The practice of regular physical exercise is related to the control of various cardiovascular diseases and other chronic diseases, such as metabolic syndrome. In this study was analyzed the metabolic profile of athletes, indoor soccer, voluntary, female with an average age of 20.5 years (2.5) of a female team, which train of 5 (five) to 6 (six) twice week, and compared the levels of bearers of the metabolic syndrome. Blood samples were collected from athletes and conducted tests for levels of glucose, total cholesterol and triglycerides, as well as the lifting of the Body Mass Index, BMI. Compared to the standards of WHO for carriers of the syndrome X, the athletes are in the patterns considered normal, strengthening the hypothesis that physical exercise is important in the control of these diseases.